Vegetasi Pantai sebagai Apotek Alam: Keragaman Spermatophyta Berkhasiat Obat dan Peluang Pemanfaatannya - Suharno Zen; Rinta Aprilia; Miftahuz Zakiyah; Nadya Syarifatul Fajriyah; Ilham Fathurrahman (Jurnal Sains Biomedis, 2025)
One of the plant groups that dominate coastal vegetation is Spermatophyta, which not only has an ecological function as a coastal protector and erosion prevention, but also has great potential as a medicinal plant. This study aims to explore the diversity and potential of coastal vegetation plants as a source of natural medicine that can be used for traditional and modern medicine. In this study, identification of the types of plants that grow along the coast was carried out. The method used includes collecting plant samples, This type of research is descriptive. The method used is purposive sampling with the line transect technique. Determination of 3 locations as sampling stations at Tanjung Setia Krui Beach, West Lampung. Furthermore, the results of the inventory were identified using the Spermatophyta identification book. The research results found 11 plant species that have the potential as natural medicinal plants, namely kelapa (Cocos sp), sea pandan (Pandanus tectorius), ketapang (Terminalia catappa), tapak liman (Elephantopus scaber), beluntas (Pluchea indica), babandotan/bandotan (Ageratum conyzoides), waru (Hibiscus tiliaceus), krokot (Portulaca oleracea), ornamental beans (Arachis pintoi), butun or keben (Barringtonia asiatica) and katang (Ipomea pes-caprae). The Diversity Index (H’) of higher plants that make up coastal vegetation at Tanjung Setia Krui Beach is 1.061. So it is categorized as moderate, the Dominance Index (ID) of station 1 is 0.112, station 2 is 0.108, station 3 is 0.358. So it is categorized as low. This study provides knowledge about the potential for utilizing coastal vegetation plants as sustainable natural resources, the development of natural medicinal products, especially in the use of natural materials as an alternative treatment.